2023
DOI: 10.1371/journal.pmed.1004143
|View full text |Cite
|
Sign up to set email alerts
|

Regional and country-level trends in cervical cancer screening coverage in sub-Saharan Africa: A systematic analysis of population-based surveys (2000–2020)

Abstract: Background Sub-Saharan Africa (SSA) has the highest cervical cancer (CC) burden globally—worsened by its HIV epidemics. In 2020, the World Health Organization (WHO) introduced a CC elimination strategy with goals for vaccination, screening, and treatment. To benchmark progress, we examined temporal trends in screening coverage, percent screened at least twice by the age of 45, screening coverage among women living with HIV (WLHIV), and pre-cancer treatment coverage in SSA. Methods and findings We conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…To note, in our included cohort of WLWH in 2021, 58% had undergone a pap smear test, which is an increase compared to the 27% who had undergone a pap smear in our previously studied cohort at the HIV clinic in 2015 [11]. The current percentage of women living with HIV who had been screened is higher than the one estimated for Rwanda in previous reports [37]. It is currently unknown whether the increase in cervical cancer screening in Rwanda also includes other women than risk patients for cervical cancer.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…To note, in our included cohort of WLWH in 2021, 58% had undergone a pap smear test, which is an increase compared to the 27% who had undergone a pap smear in our previously studied cohort at the HIV clinic in 2015 [11]. The current percentage of women living with HIV who had been screened is higher than the one estimated for Rwanda in previous reports [37]. It is currently unknown whether the increase in cervical cancer screening in Rwanda also includes other women than risk patients for cervical cancer.…”
Section: Discussionmentioning
confidence: 54%
“…The likelihood of being cervical cancer screened is higher in WLWH than in HIVnegative women in East Africa [37]. To note, in our included cohort of WLWH in 2021, 58% had undergone a pap smear test, which is an increase compared to the 27% who had undergone a pap smear in our previously studied cohort at the HIV clinic in 2015 [11].…”
Section: Discussionmentioning
confidence: 75%
“…As more frequent cervical cancer screening is recommended for WLWH, 27,28 detection bias might have contributed to the higher cervical precancer and cancer rates we found among WLWH compared to women without HIV. We lacked comprehensive data on cervical cancer screening to assess this hypothesis in our study, but a systematic study of population‐based surveys found that the odds of cervical cancer screening were similar in WLWH and women without HIV in Southern Africa 29 …”
Section: Discussionmentioning
confidence: 99%
“…The proportion of women aged 30-49 in Sub-Saharan Africa who had ever received a cervical screen has been estimated at 3-5% (20), although among countries for which survey or other reported data were available, coverage was estimated to be higher, at around 14% (21,22). Across the four countries that had published survey data on precancer treatment, coverage was estimated at around 80% (21). Substantial variation in both the coverage levels and the quality of screening programs has been reported.…”
Section: Modeling Interventionsmentioning
confidence: 99%